(3GdJMaI GdSfjI ddMVQI GdTQjaI GdMSjfjIs - (3GdcQOhOjs
(3ChdgG (B:s
(3hHYO adeG hbY GdJZdH ef CYOGA GdOjf Ydi HYV HdGOGJ GdeSdejf cJhfS heUQ s
(3BNQgG (B:s
(3hdG Mhd hdG bhI EdG HGddg GdYdi GdYXje hUdi Gddg Ydi SjOfG hehdGfG eMeO hCdg hUMHg CLeYjf hSde JSdjekG cKjQkG Edi jhe GdOjf hGdMeO ddg QH GdYGdejf GfJgi hGdMeO ddg ChdkG hENQkG HGWfkG hXGgQkG s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B- (3GdeZQH (B(1282(3O(B) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs